2023
DOI: 10.3389/fpubh.2023.1129797
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight, obesity, and associated factors among healthcare workers in the Gaza Strip, Palestine: A cross-sectional study

Abstract: BackgroundOverweight and obesity are multifactorial conditions that are prevalent in developing and developed countries. They are emerging as a significant public health concern among healthcare workers (HCWs). We aimed to estimate the prevalence of overweight and obesity and their associated factors among HCWs in the Gaza Strip.MethodsA cross-sectional study was conducted to recruit 1,850 HCWs aged 22 years and older. Interviews were carried out to collect sociodemographic information, nutritional information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…On the other hand, the magnitude of central obesity in this study is comparable to the magnitude of central obesity among health workers in Gaza strips in Palestine [34], two studies that found 24.6%, and 27.7% of central obesity among public service workers in the United States of America(USA) [35,36].…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, the magnitude of central obesity in this study is comparable to the magnitude of central obesity among health workers in Gaza strips in Palestine [34], two studies that found 24.6%, and 27.7% of central obesity among public service workers in the United States of America(USA) [35,36].…”
Section: Discussionsupporting
confidence: 73%
“…However, in our study, significant differences were recorded in the physical activity sub-dimension ( p < 0.001) among nurses employed for more than 30 years who reported higher levels of physical activity (5.25 ± 0.23) than the other groups. In this regard, the literature showed that physical activities among nurses have demonstrated an arrangement of non-adherence to public health guidelines, diet, smoking and alcohol assumption [ 8 , 48 ], by leading overweight and obesity conditions, as shown in an English national survey that highlighted a high prevalence of obese nurses than other healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…Height and weight measurements were utilized to calculate the BMI, with BMI values falling below 18.5 kg/m2 indicating underweight, values between 18.5 and 24.9 kg/m2 indicating normal weight, values between 25 and 29.9 kg/m2 indicating overweight, and values equal to or exceeding 30 kg/m2 indicating obesity. [19][20][21] Waist circumference measurements are based on the guidelines set forth by the International Diabetes Federation, with waist circumference values ≤ 90 cm for males and ≤ 80 cm for females classified as waist 1, values between 90 and 102 cm for males and 80 and 88 cm for females classified as waist 2, and values exceeding 102 cm for males and exceeding 88 cm for females classified as waist 3. The third section is specifically designed to gather data about physical activity and is adapted from the concise version of the International Physical Activity Questionnaire (IPAQ-short version).…”
Section: Data Collectionmentioning
confidence: 99%
“…Lastly, the fifth section entails the collection of data on comorbid conditions such as diabetes mellitus (DM), hypertension, and dyslipidemia. [20,21].…”
Section: Data Collectionmentioning
confidence: 99%